Relationship Between COVID-19 Related Knowledge and Anxiety Among University Students: Exploring the Moderating Roles of School Climate and Coping Strategies - Quansah, Frank; Hagan, John E.; Ankomah, Francis; Srem-Sai, Medina; Frimpong, James B.; Sambah, Francis; Schack, Thomas (Frontiers in Psychology, 2022)
The emergence of Covid-19 pandemic resulted in abrupt disruptions in teaching and learning activities in higher education, with students from diverse programmes suffering varied levels of discomfort and insecurity. Physical Education field happen to be one of the most affected academic areas due to its experiential content as a medium of instruction. In this study, we investigated the roles of school climate and coping strategies in the relationship between Covid-19 related knowledge and anxiety. Through census approach, a cross-sectional sample of 760 students were administered a questionnaire in two universities offering Physical Education in Ghana: University of Education, Winneba, and University of Cape Coast. The outcome of the study revealed a positive and significant link between Covid-19 knowledge and anxiety. Furthermore, school climate and coping strategies significantly moderated the relationship between students’ Covid-19 knoweldge and their associated anxiety. The findings have implications for creating proactive school environment, free from Covid-19 infections as well as students adopting active coping strategies in attempt to reduce psychological distress associated with Covid-19 anxiety.